PENGARUH KOMUNIKASI, STRESS KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. SAGA DENPASAR - I Putu Randy Sastrawan; I Nengah Sudja; Yenny Verawati (VALUES, 2022)
One of the factors that influence the level of success of an organization is the performance of its employees. In order for management activities to run well, companies must have knowledgeable employees and efforts to manage the company as optimally as possible so that employee performance increases. This study aims to examine and obtain empirical evidence of the effect of communication, job stress and compensation on employee performance at PT. SAGA Denpasar. The object of research in this research is communication, work stress, and compensation for employee performance at PT. SAGA Denpasar. The total population in this study was 72 people. The method of determining the sample using the saturated sampling method. The number of samples in this study was 72 respondents. Methods of data collection using a observation, Interview, and questionnaire. The data analysis technique used multiple linear regression analysis. The results showed that communication had a positive and significant effect on employee performance at PT. SAGA Denpasar. Work stress has a negative and significant effect on employee performance at PT. SAGA Denpasar. Compensation has a positive and significant effect on employee performance at PT. SAGA Denpasar.